32.1 W/m2 continuous wave solar-pumped laser with a bonding Nd:YAG/YAG rod and a Fresnel lens. (November 2018) - Guan, Z.; Zhao, C.; Li, J.; He, D.; Zhang, H.
Highlights: The first time a bonding Nd:YAG/YAG crystal was investigated in solar-pumped laser. A collection efficiency of 32.1 W/m 2 was achieved in solar laser system. The bonding crystal rod has shown excellent performance in laser beam quality. Abstract: We report here significant progress in solar-pumped laser collection efficiency with a grooved bonding Nd:YAG/YAG crystal rod. A Fresnel lens was used as the primary solar radiation concentrator. A gold-plated conical pump cavity with a water filled quartz tube lens was used to concentrate the solar radiation from the focal zone of the primary concentrator into a 6-mm-diameter, 95-mm-length bonding Nd:YAG/YAG crystal rod. To the best of our knowledge, it is the first time of a bonding Nd:YAG/YAG crystal pumped by Fresnel lens solar energy collection and concentration system. For 1.03 m 2 effective solar radiation collection area, 32.1 W/m 2 collection efficiency was obtained, corresponding to a total slope efficiency of 5.4% and an optical-to-optical efficiency of 3.3%. The performance of the grooved bonding crystal rod was compared with the grooved non-bonding crystal rod. The maximum output power from the grooved bonding crystal rod was 22.6% higher than the value from a grooved non-bonding rod. The M 2 beam quality factor was also improved from 126 to 61.